Design and characterization of a novel nanocomposite: Synergistic integration of rhodium, carbon fiber, and cobalt via CES Edu pack - Ostergllava, Naim (Edelweiss Applied Science and Technology, 2025)
This paper presents the development and comprehensive characterization of an advanced nanocomposite achieved through the strategic integration of rhodium, carbon fiber, and cobalt. Utilizing CES Edu Pack for in-depth material analysis, the study evaluates the mechanical, thermal, and magnetic properties of each constituent and their synergistic interactions when combined. The experimental findings indicate that a composite formulation consisting of 10% rhodium, 80% carbon fiber, and 10% cobalt achieves an optimal balance of high modulus of elasticity, enhanced durability, and improved flexibility. Rhodium provides exceptional corrosion resistance and thermal stability; carbon fiber contributes a superior strength-to-weight ratio and excellent electrical conductivity; and cobalt enhances the composite’s magnetic properties and overall mechanical performance. The resulting nanocomposite demonstrates significant potential for application in high-performance technologies, including flexible sensors, advanced electronic devices, and nanomedicine platforms. This work lays a robust foundation for future research aimed at further optimizing composite materials for next-generation technological innovations.